Effective removal of copper ion from aqueous solution using beads of chitosan-choline chloride or glycerol deep eutectic solvent / Nur Hidayah Sazali ... [et al.] - Sazali, Nur Hidayah; Kong, Sein Ann; Mohd Suah, Faiz Bukhari; Miskam, Mazidatulakmam; Rahim, Nurul Yani (Universiti Teknologi MARA Shah Alam, 2022)
Herein, adsorption process based on new adsorbent was utilized to remove copper ion (Cu(II)), an environmental pollutant, from water. The reprocessing of powder chitosan into a highly porous bead would have the advantage for the industrial treatment of water. Chitosan-deep eutectic solvent (DES) beads were prepared from chitosan and DESs. The DESs used were choline chloride-urea (DES A) and choline chloride-glycerol (DES B). Both chitosan-DES beads were used to remove Cu(II) from an aqueous solution. Based on the characterisation results, chitosan-DES A showed a higher chemical and thermal stability when compared to chitosan-DES B. For type of adsorbents, chitosan-DES B showed a higher removal percentage of Cu(II) (90.92 %) than chitosan-DES A (7.5 %). Therefore, chitosan-DES B was chosen as the preferred adsorbent for Cu(II). The optimum conditions for the removal of Cu(II) from aqueous solution were using 0.09 g of chitosan-DES B with 40 min of shaking time and 1 mg L-1 of initial concentration.